1999
DOI: 10.1105/tpc.11.11.2153
|View full text |Cite
|
Sign up to set email alerts
|

Pht2;1 Encodes a Low-Affinity Phosphate Transporter from Arabidopsis

Abstract: An Arabidopsis genomic sequence was recently shown to share similarity with bacterial and eukaryotic phosphate (Pi) transporters. We have cloned the corresponding cDNA, which we named Pht2;1 , and subsequently performed gene expression studies and functional analysis of the protein product. The cDNA encodes a 61-kD protein with a putative topology of 12 transmembrane (TM) domains interrupted by a large hydrophilic loop between TM8 and TM9. Two boxes of eight and nine amino acids, located in the N-and C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 179 publications
(91 citation statements)
references
References 47 publications
3
88
0
Order By: Relevance
“…The Pht2 family of plant Pi transporters Subsequent to Pi uptake at the root-soil interface, it can be expected that (at least) three additional transport systems participate in Pi translocation within the plant: (i) secretion of Pi into the root xylem; (ii) loading of leaf cells with Pi from the vascular system; and (iii) loading (Daram et al 1999); MEScry;Pht2;1 (U84890) from Mesembryanthemum crystallinum; A.ful (AE000978) from Archaeoglobus fulgidus; H.inf (P45268) from Haemophilus influenza; PHO4 (JQ0116) from Neurospora crassa (Mann et al 1989;Versaw and Metzenberg 1995); PHO89 (P38361) from Saccharomyces cerevisiae ; GLVR1 (L20859) from Homo sapiens (Kavanaugh et al 1994;Olah et al 1994); Ram-1 (L19931) from Rattus norvegicus (Kavanaugh et al 1994;Miller et al 1994); and C.ele (U50312) from Caenorhabditis elegans; LePT1 (O24029) and LePT2 (O22549) from Lycopersicon esculentum (Daram et al 1998;Liu et al 1998a); StPT1 (Q43650) and StPT2 (Q41479) from Solanum tuberosum (Leggewie et al 1997); PHO84 (P25297) from S. cerevisiae (Bun-Ya et al 1991). PHO4, PHO89, Ram-1 and GLVR1 were characterised as Na + /Pi symporters, while ARAth;Pht2;1 is a H + /Pi symporter, as described in the cited papers.…”
Section: Pi Transport In Mycorrhizaementioning
confidence: 99%
See 1 more Smart Citation
“…The Pht2 family of plant Pi transporters Subsequent to Pi uptake at the root-soil interface, it can be expected that (at least) three additional transport systems participate in Pi translocation within the plant: (i) secretion of Pi into the root xylem; (ii) loading of leaf cells with Pi from the vascular system; and (iii) loading (Daram et al 1999); MEScry;Pht2;1 (U84890) from Mesembryanthemum crystallinum; A.ful (AE000978) from Archaeoglobus fulgidus; H.inf (P45268) from Haemophilus influenza; PHO4 (JQ0116) from Neurospora crassa (Mann et al 1989;Versaw and Metzenberg 1995); PHO89 (P38361) from Saccharomyces cerevisiae ; GLVR1 (L20859) from Homo sapiens (Kavanaugh et al 1994;Olah et al 1994); Ram-1 (L19931) from Rattus norvegicus (Kavanaugh et al 1994;Miller et al 1994); and C.ele (U50312) from Caenorhabditis elegans; LePT1 (O24029) and LePT2 (O22549) from Lycopersicon esculentum (Daram et al 1998;Liu et al 1998a); StPT1 (Q43650) and StPT2 (Q41479) from Solanum tuberosum (Leggewie et al 1997); PHO84 (P25297) from S. cerevisiae (Bun-Ya et al 1991). PHO4, PHO89, Ram-1 and GLVR1 were characterised as Na + /Pi symporters, while ARAth;Pht2;1 is a H + /Pi symporter, as described in the cited papers.…”
Section: Pi Transport In Mycorrhizaementioning
confidence: 99%
“…The molecular components involved in this (active or passive) efflux of Pi across the arbuscular membrane are not known and the mechanisms underlying the process are not understood (Smith and Read 1997), while Pi uptake into the cortical cells was suggested to involve a H + -coupled symport mechanism. A lead-precipitation method used to visualise - Daram et al (1999) h Eicks et al (2002) ATPase activity (Gianinazzi-Pearson et al 1991), immunolabelling of H + -ATPase protein, and H + -ATPasepromoter-GUS assays (Gianinazzi-Pearson et al 2000) revealed that the periarbuscular membrane contains high H + -ATPase activity. Additionally, it was shown that arbuscules inhabit an acidic compartment within plant roots, which can be destroyed by treatment with a protonophore or by membrane rupture (Guttenberger 2000).…”
Section: Pi Transport In Mycorrhizaementioning
confidence: 99%
“…In this pathway, an electrochemical gradient must be generated across the plasma membrane for Pi uptake, which is coupled to cotransport cations, often H + , and it is mediated by Pi transporters localized at the plasma membrane (Schachtman et al, 1998 ;Daram et al, 1999 ;Bucher, 2007 ). Pioneering work carried out by Emmanuel Epstein and later contributions demonstrated that Pi uptake is a dual -phasic process that follows Michaelis -Menten kinetics (Epstein, 1976 ;Aung et al, 2006 ).…”
Section: Direct Phosphate Uptake Pathwaymentioning
confidence: 99%
“…In this way, depending on external Pi concentration, low or high -affi nity transport mechanisms operate. Plant Pi transporters assisting in one or the other system have been identifi ed experimentally or predicted with the recent massive sequencing of plant genomes, and grouped into three families: Pht1, Pht2, and Pht3 (Muchhal et al, 1996 ;Smith et al, 1997 ;Okumura et al, 1998 ;Daram et al, 1999 ;Rausch and Bucher, 2002 ).…”
Section: Direct Phosphate Uptake Pathwaymentioning
confidence: 99%
See 1 more Smart Citation